CORPORATE DIVESTITURE INTENSITY IN RESTRUCTURING FIRMS: EFFECTS OF GOVERNANCE, STRATEGY, AND PERFORMANCE. - HOSKISSON, R. E.; JOHNSON, R. A.; MOESEL, D. D. (Academy of Management Journal, 1994)
Both inadequate governance and inappropriate strategy have been proposed as antecedents of the divestment activity of restructuring firms in the 1980s. We combined both views in a structural equati...